Neuro-ophthalmological abnormalities in patients with ischemic stroke in the setting of a stroke center of a university clinic - T. M. Muratova; L. V. Venger; D. M. Khramtsov; Iu. M. Vorokhta; V. D. Teliushchenko (Ukrainian Society of Ophthalmologists, 2020)
Background: Stroke remains one of the leading causes of death and disability in the world. Most patients with stroke exhibit neuro-ophthalmological abnormalities. Purpose: To assess the frequency of neuro-ophthalmological abnormalities in patients with stroke in the setting of a stroke center of a university clinic. Material and Methods: Two hundred and ninety-eight patients with acute ischemic cerebrovascular accidents who were under observation at the stroke service of the Neurology Department of the Center for Reconstructive and Restorative Medicine (University Clinic) of the Odesa National Medical University from January 2016 through December 2019 were included in the study. Frequency of neuro-ophthalmological symptoms was assessed at the first neurological examination visit and after ophthalmologist consultation was obtained. Results: Of the 298 patients with stroke, most (162; 54%) were men. Mean patient age was 60.4 ± 1.1 years and mean National Institutes of Health Stroke Scale (NIHSS) score was 10.1 ± 0.9. In addition, of the 298 patients, 163 (54.7%) were admitted to the clinic within a day after onset of clinical symptoms of a stroke. Stroke syndromes were categorized into four subtypes, total anterior circulation infarcts (TACI), partial anterior circulation infarcts (PACI), lacunar circulation infarcts (LACI), and posterior circulation infarcts (POCI). PACI were the most common (139 cases or 36.6%), followed by LACI (88 cases or 29.5%), whereas TACI were least common (28 cases or 10.5%). Of special interest were POSI (43 cases or 14.4%). Fourteen patients with POSI (4.7% of the total study patients) had lesions of the midbrain and pons. Neuro-ophthalmological manifestations were found in 88.8% of patients. Of these manifestations, anisocoria was the most common (60.1%), followed by hemianopia (27.9%), diplopia (22.1%) and visuospatial neglect (19.5%), and various oculomotor abnormalities. Internuclear ophthalmoplegia (INO) was found only in 8 cases (2.7%). Conclusion: Diagnosing neuro-ophthalmological syndromes requires coordinated efforts of the neurologist and ophthalmologist in the setting of a multi-professional team.